Two-dimensional double-metal porphyrin composite material covered by in-situ TiO2 nano particle layer and preparation and application of two-dimensional double-metal porphyrin composite material
By preparing the TiO2 nanoparticle layer covered with two-dimensional bimetaloporphyrin composite in situ, the existing TiO2 photocatalysts have been solved, and high efficiency photocatalytic hydrogen production under the full spectrum is achieved.
Patent Information
- Application Number
- CN202411618566.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-25
AI Technical Summary
The existing TiO2 photocatalyst has low photocatalytic efficiency and has problems such as high material cost, large synthesis complexity and insufficient stability in industrial applications.
By preparing the TiO2 nanoparticle layer in situ, the two-dimensional bimetaloporphyrin composite material is hydrolyzed and crystallized under hydrogen bonding using tetrabutyl titanate and two-dimensional bimetaloporphyrin MOFs to form a composite material with a uniform TiO2 nanoparticle layer.
High efficiency of photocatalytic hydrogen production under the full spectrum is achieved, the catalyst synthesis process is simple, the photocatalytic activity is excellent, and precious metal cocatalysts are not required.
Smart Images

Figure CN119680644A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysts, and in particular to a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer, and the preparation and application thereof. Background Art
[0002] The continuous consumption of fossil fuels is exacerbating the global energy shortage and environmental crisis, leading to a series of serious problems such as climate change, air pollution and ecosystem destruction. Therefore, it has become a top priority to develop sustainable energy to replace traditional fossil fuels. Photocatalytic hydrogen evolution, as an emerging clean energy technology, has attracted widespread attention by using light energy to decompose water into hydrogen and oxygen. Hydrogen, as a renewable clean energy, can effectively replace traditional fossil fuels and help solve energy crises and environmental problems. Photocatalysts are the key to achieving photocatalytic hydrogen evolution. In recent years, researchers have developed a variety of photocatalytic materials, including semiconductor materials (such as TiO2, ZnO, CdS, etc.) and precious metal catalysts (such as Pt, Pd, etc.). The light absorption characteristics and catalytic activity of different materials have a significant effect on the efficiency of hydrogen evolution. In recent years, researchers have also explored composite materials and doping techniques to improve the performance and stability of photocatalysts.
[0003] As photocatalytic hydrogen evolution materials, two-dimensional metal organic frameworks show great potential due to their high specific surface area, excellent optical properties, good conductivity and adjustability. This makes them a promising catalyst choice in the development and application of renewable energy. With the deepening of research, the application of 2D MOFs in the field of photocatalysis will be more extensive, promoting the progress of clean energy technology. The combination of inorganic semiconductors and metal organic frameworks, as an effective strategy, can significantly enhance the charge separation efficiency and improve the stability of MOFs. TiO2, as a photocatalyst that exhibits good stability and low cost under ultraviolet radiation, is an ideal candidate for synergistic interaction with metal organic frameworks (MOFs). However, TiO2 alone has a wide band gap, absorbs only about 5% of ultraviolet light in the solar spectrum, and has a fast recombination rate of photogenerated hole-electron pairs. This problem significantly reduces the photocatalytic efficiency of TiO2 and limits its industrial application.
[0004] Patent Publication No. CN112473638A discloses a ruthenium-doped ultra-thin TiO2 nanosheet photocatalyst. In the process of preparing ultra-thin TiO2 nanosheets by hydrothermal reaction, ruthenium ions are doped into the nanosheet layer structure to obtain a highly stable and highly active photocatalyst Ru-TiO2. Although the doping of ruthenium makes the nanosheets highly active and stable, the material cost, synthesis complexity and large-scale application still need to be further optimized and studied. Patent Publication No. CN113398997A discloses a platinum-doped ultra-thin Zr-MOFs nano-thin layer composite photocatalyst, which exhibits high stability during the reaction process and maintains its catalytic performance under long-term illumination, reducing catalyst deactivation. The high specific surface area and adjustability of MOFs materials make the catalyst have better reactivity and adsorption capacity, but the control requirements for reaction conditions and processes are high, which may affect the uniformity and performance of the catalyst, and may face the problem of reduced efficiency and stability in industrial applications. Patent Publication No. CN104324760A discloses a method for preparing and applying a functional coordination polymer, and obtains a functionalized coordination polymer Ag@MOF@TiO2. The composite material has the synergistic effect of nanosilver, MOF and TiO2, and has industrial application prospects. Although the scheme has achieved a high yield in the preparation, the complexity of its synthesis process involves multiple synthesis steps, including the preparation of Ag@MOF and the coating of TiO2, which may lead to complex and time-consuming operations. In addition, it involves multiple chemical reagents and reaction conditions, making the optimization of each step difficult. At the same time, the sensitivity to conditions, high-cost raw materials, product purity and functional limitations, stability, recovery difficulty and other issues may pose challenges in practical applications. The above three methods have improved the photocatalytic activity of TiO2 and MOFs materials to a certain extent, but the complexity of the synthesis and the introduction of precious metals as co-catalysts are relatively expensive. Moreover, in the commonly reported methods, due to the rapid formation of TiO2, TiO2 nanoparticles are easily self-aggregated, resulting in insufficient interfacial contact between the obtained TiO2 nanoparticles and the two-dimensional bimetallic porphyrin MOFs, which is not conducive to the efficient transfer of photogenerated electrons and the improvement of photocatalytic activity. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer and its preparation and application. The TiO2 nanoparticle layer is introduced into the surface of the two-dimensional bimetallic porphyrin composite material through in-situ preparation to improve the photocatalytic efficiency of the two-dimensional bimetallic porphyrin composite material. High-efficiency photocatalytic hydrogen production under the full spectrum can be achieved without the introduction of precious metal co-catalysts. The catalyst synthesis process is relatively simple and the photocatalytic activity is excellent.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer, wherein tetrabutyl titanate is mixed with two-dimensional bimetallic porphyrin MOFs (Zn-TCPP(Cu)MOF, abbreviated as ZnTCuM) in a first solvent system and heated to reflux, and the obtained solid product is subjected to a solvothermal reaction in a second solvent system to obtain a two-dimensional bimetallic porphyrin composite material (Zn-TCPP(Cu)MOF TiO2, abbreviated as ZnTCuMT) covered with an in-situ TiO2 NPs (titanium dioxide nanoparticle) layer, and the reaction is completed.
[0008] Furthermore, the mass volume ratio of the two-dimensional bimetallic porphyrin MOFs to tetrabutyl titanate is 2:25-100 mg / μL.
[0009] Further, the mixture is heated under reflux at a temperature of 60 to 120° C. and a reaction time of 2 to 8 h;
[0010] The first organic solvent used in the first solvent system includes a mixture of water and ethanol;
[0011] In the solvent thermal reaction, the temperature is 100-150°C and the reaction time is 8-16h;
[0012] The second organic solvent used in the second solvent system includes a mixture of water and N,N-dimethylformamide.
[0013] Furthermore, when the first solvent is a mixture of water and ethanol, the volume ratio of water to ethanol is (5-30):(10-50).
[0014] Furthermore, when the second organic solvent is a mixture of water and N,N-dimethylformamide, the volume ratio of water to N,N-dimethylformamide is (5-30):(0.1-0.4).
[0015] Furthermore, the preparation process of the two-dimensional bimetallic porphyrin MOFs is: tetrakis(4-carboxyphenyl)porphine (TCPP), benzoic acid, copper salt, and zinc salt are mixed in a third organic solvent, and heated under reflux reaction to obtain the two-dimensional bimetallic porphyrin MOFs.
[0016] Furthermore, TCPP, benzoic acid, copper salt and zinc salt are added to the third organic solvent in sequence and mixed.
[0017] Furthermore, the copper salt includes copper chloride and copper nitrate;
[0018] The zinc salts include zinc nitrate and zinc chloride;
[0019] The third organic solvent includes N,N-dimethylformamide, ethanol or a mixture thereof;
[0020] The molar ratio of TCPP, benzoic acid, copper salt and zinc salt is 1:(2-6):(7-14):(4-10);
[0021] In the heating reflux reaction, the reaction temperature is 120-180°C and the reaction time is 1-6h.
[0022] Furthermore, when the third organic solvent is a mixture of N,N-dimethylformamide and ethanol, the volume ratio of N,N-dimethylformamide to ethanol is 5 to 50:1.
[0023] Furthermore, the TCPP and benzoic acid are first added to the third organic solvent, heated, and then copper salt and zinc salt are added, and the obtained mixture is heated and refluxed to obtain two-dimensional bimetallic porphyrin MOFs.
[0024] Furthermore, after heating under reflux reaction, the obtained solid is washed and dried to obtain two-dimensional bimetallic porphyrin MOFs.
[0025] Furthermore, the drying is vacuum drying at a temperature of 40 to 80°C.
[0026] Furthermore, tetrabutyl titanate is dispersed in a fourth organic solvent and preheated, and the fourth organic solvent includes ethanol.
[0027] Furthermore, the preheating temperature of the tetrabutyl titanate is 50-100° C., and the preheating time is 1-3 hours.
[0028] Furthermore, tetrabutyl titanate is preheated, mixed with the two-dimensional bimetallic porphyrin MOFs in a first solvent system, heated to reflux, centrifuged to obtain a solid product, washed, and the washed solid product is subjected to a solvothermal reaction in a second solvent system. The product is collected by centrifugation, washed, and dried to obtain a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer, and the reaction is completed.
[0029] Furthermore, the detergent used for washing is ethanol.
[0030] Furthermore, the drying is vacuum drying at a temperature of 40 to 80°C.
[0031] The second technical solution of the present invention is to provide a two-dimensional bimetallic porphyrin composite material covered by an in-situ TiO2 nanoparticle layer, which is prepared by the above-mentioned preparation method, and the two-dimensional bimetallic porphyrin composite material covered by the in-situ TiO2 nanoparticle layer. Compared with physically mixed TiO2 nanoparticles and two-dimensional bimetallic porphyrin MOFs, the in-situ grown TiO2 nanoparticle layer is more uniform on the two-dimensional bimetallic porphyrin MOFs sheet, the interface contact is closer, and the interface resistance is also lower, so the charge separation efficiency and photocatalytic activity are higher, the photocurrent is increased by 6-9 times, the impedance is reduced by 2-4 times, and the hydrogen evolution rate is increased by 2-6 times.
[0032] The third technical solution of the present invention is to provide a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer for use in the field of photocatalytic hydrolysis to produce hydrogen.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] (1) The present invention improves the dispersion and binding of tetrabutyl titanate on two-dimensional bimetallic porphyrin MOFs through hydrogen bonding between the two-dimensional bimetallic porphyrin MOFs and tetrabutyl titanate, and then obtains a two-dimensional bimetallic porphyrin composite material with a uniform TiO2 nanoparticle layer on the surface through in-situ hydrolysis and crystallization of tetrabutyl titanate. The two-dimensional bimetallic porphyrin MOFs are used to improve the visible light absorption of TiO2, and the close interface interaction between the TiO2 nanoparticle layer and the two-dimensional bimetallic porphyrin MOFs is used to improve the photogenerated charge separation and the stability of the two-dimensional bimetallic porphyrin MOFs, and finally a TiO2 / porphyrin MOFs composite photocatalytic material with high photocatalytic hydrogen production efficiency and cyclic stability is obtained.
[0035] (2) The present invention mixes ZnTCuM and TiO2 materials, heats them under reflux, and then performs a solvent thermal reaction to obtain a two-dimensional bimetallic porphyrin composite material having a uniform TiO2 nanoparticle layer covering the surface. The in-situ synthesis of TiO2 NPs particles means that TiO2 is directly synthesized in the presence of ZnTCuM. This method can improve the interaction between TiO2 and ZnTCuM, and enhance the structural stability and catalytic performance of the composite material.
[0036] (3) Among the many methods for improving photocatalytic efficiency, constructing a composite material of metal organic framework (MOF) and semiconductor TiO2 is a very promising strategy. The copper ions in ZnTCuM can introduce specific energy levels in the band gap of TiO2 semiconductor, promote the absorption of long-wavelength light, thereby broadening the light response range of TiO2 and significantly enhancing its photocatalytic performance. As a molecule with a highly conjugated structure, two-dimensional bimetallic porphyrin MOFs are widely used in the field of photocatalysis. Their excellent optical properties and low energy barriers accelerate their electron transfer rate. In the present invention, the light response range of TiO2 NPs particles is broadened, thereby enhancing the overall photocatalytic performance. In addition, the presence of ZnTCuM helps to effectively suppress the recombination phenomenon of electron-hole pairs during the catalytic process, further improving the catalytic activity. Therefore, in order to overcome the existing defects, the present invention prepares a new type of organic-inorganic heterogeneous photocatalyst by introducing a TiO2NPs particle layer onto the surface of ZnTCuM.
[0037] (4) In the two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer constructed in this application, the active TiO2 NPs layer grows in-situ on the two-dimensional bimetallic porphyrin MOFs, effectively protecting the two-dimensional bimetallic porphyrin MOFs from corrosion, improving its photocatalytic stability and charge separation, while the two-dimensional bimetallic porphyrin MOFs increase visible light absorption, and the multi-metal center provides more active sites, and the moderate TiO2 NPs layer tightly bound to the two-dimensional bimetallic porphyrin MOFs sheet can improve the electron transfer of the composite photocatalyst. Compared with similar photocatalytic materials, its photocatalytic hydrogen evolution activity and stability are significantly improved.
[0038] (5) This application can realize high-efficiency photocatalytic hydrogen production catalyst under the full spectrum without the introduction of precious metal co-catalysts. At the same time, the light absorption, photogenerated charge separation and photocatalytic cycle stability of the TiO2 photocatalytic material and the two-dimensional bimetallic porphyrin MOFs are improved, and a new and efficient two-dimensional bimetallic porphyrin MOFs composite photocatalytic material with a TiO2 nanoparticle layer on the surface is developed.
[0039] (6) Compared with other methods that require step-by-step processing, the present invention is achieved through simple mixing and heating reflux, which reduces the material processing steps in the synthesis process, simplifies the experimental process, and improves efficiency. The active TiO2 NPs particle layer can effectively protect ZnTCuM from corrosion, and ZnTCuM can provide more active centers and light absorption, thereby improving the photocatalytic hydrogen evolution activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 N2 adsorption-desorption isotherms of photocatalysts (a) ZnTCuM and (b) ZnTCuMT;
[0041] Figure 2 The hydrogen production kinetic curves of photocatalysts (a) TiO2, (b) ZnTZnM, (c) ZnTCuM, (d) ZnTZnMT, (e) ZnTCuMT;
[0042] Figure 3 A comparison chart of hydrogen evolution rates of ZnTCuMT, FeTCuMT, AlTCuMT, CoTCuMT, and CuTCuMT photocatalysts prepared in Example 2 and Comparative Examples 8 to 11;
[0043] Figure 4 The hydrogen evolution kinetic curves of FeTMT and FeTCuMT photocatalysts in 50 mL deionized water and 10 mL TEOA;
[0044] Figure 5 Hydrogen evolution kinetics curves of AlTMT and AlTCuMT photocatalysts in 50 mL deionized water and 10 mL TEOA;
[0045] Figure 6 The fluorescence spectra of TiO2, ZnTCuM, ZnTCuMT and ZnTCuM-TiO2 photocatalysts are shown;
[0046] Figure 7 The comparison results of the photocurrent spectra of TiO2, ZnTCuM, ZnTCuMT and ZnTCuM-TiO2 photocatalysts are shown in the figure;
[0047] Figure 8 This is a comparison of the photocurrent spectra of TiO2, ZnTCuM, ZnTCuMT, and ZnTCuM-TiO2 photocatalysts. DETAILED DESCRIPTION
[0048] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0049] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.
[0050] In the following examples, TCPP has a CAS number of 14609-54-2, a brand of Frontier Scientific, and is purchased from Anolun (Beijing) Biotechnology Co., Ltd.; N,N-dimethylformamide, CAS No. 68-12-2, AR, ≥99.5%, is purchased from Shanghai Titan Technology Co., Ltd.; tetrabutyl titanate, CAS No. 5593-70-4, AR., ≥98.5%, is purchased from Shanghai Titan Technology Co., Ltd.
[0051] Example 1
[0052] A two-dimensional bimetallic porphyrin composite photocatalyst (ZnTCuMT) covered with an in-situ TiO2 nanoparticle layer, the preparation method of which comprises the following steps:
[0053] (I) Preparation of ZnTCuM
[0054] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, which was labeled as mixture 1. Subsequently, 100 mg (0.587 mmol) of CuCl2·2H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1 over 5 min. The reaction was monitored using UV-visible spectroscopy until the spectrum no longer changed. Then, 100 mg (0.336 mmol) of Zn(NO3)2·6H2O dissolved in 5 mL of ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried overnight in a vacuum oven at 60 ° C to obtain ZnTCuM.
[0055] (II) Preparation of ZnTCuMT
[0056] 8 mg of ZnTCuM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 100 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The resulting solid was separated by centrifugation and washed with ethanol 3 times. The resulting solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The resulting solid was then dried overnight in a 60 ° C vacuum oven to obtain ZnTCuMT.
[0057] (III) Photocatalytic hydrogen evolution experiment
[0058] At room temperature, 10 mg of ZnTCuMT was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0059] Example 2
[0060] A two-dimensional bimetallic porphyrin composite photocatalyst (ZnTCuMT) covered with an in-situ TiO2 nanoparticle layer is substantially the same as Example 1, except that the amount of tetrabutyl titanate is adjusted from 100 μL to 200 μL in step (ii). The preparation method thereof comprises the following steps:
[0061] (I) Preparation of ZnTCuM
[0062] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, which was labeled as mixture 1. Subsequently, 100 mg (0.587 mmol) of CuCl2·2H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1 over 5 min. The reaction was monitored using UV-visible spectroscopy until the spectrum no longer changed. Then, 100 mg (0.336 mmol) of Zn(NO3)2·6H2O dissolved in 5 mL of ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried overnight in a vacuum oven at 60 ° C to obtain ZnTCuM.
[0063] (II) Preparation of ZnTCuMT
[0064] 8 mg of ZnTCuM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 200 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The obtained solid was separated by centrifugation and washed with ethanol 3 times. The obtained solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60 ° C vacuum oven to obtain ZnTCuMT.
[0065] (III) Photocatalytic hydrogen evolution experiment
[0066] At room temperature, 10 mg of ZnTCuMT was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0067] Comparative Example 1
[0068] The preparation of pure TiO2 photocatalyst material, the specific steps are as follows:
[0069] (I) Preparation of TiO2 photocatalyst
[0070] 100 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 4 hours. The obtained solid was separated by centrifugation and washed with ethanol 3 times. The obtained solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed with anhydrous ethanol 3 times. The obtained solid was then dried in a vacuum oven at 60 ° C overnight to obtain pure TiO2 material.
[0071] (II) Photocatalytic hydrogen evolution experiment
[0072] At room temperature, 10 mg of pure TiO2 material was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor. The reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0073] Comparative Example 2
[0074] The preparation of two-dimensional metalloporphyrin Zn-TCPP(Zn)MOF(ZnTZnM) photocatalyst material, the specific steps are as follows:
[0075] (I) Preparation of two-dimensional metalloporphyrin Zn-TCPP(Zn)MOF (ZnTZnM)
[0076] 40 mg (0.049 mmol) TCPP and 25 mg (0.205 mmol) benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL DMF and heated at 150 ° C, marked as mixture 1. Then, 100 mg (0.336 mmol) Zn (NO3) 2·6H2O dissolved in 5 mL ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and subsequently dried in a vacuum oven at 60 ° C overnight to obtain ZnTZnM.
[0077] (II) Photocatalytic hydrogen evolution experiment
[0078] At room temperature, 10 mg ZnTZnM was added to an aqueous solution containing 50 mL deionized water and 10 mL triethanolamine (sacrificial agent), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp for photocatalytic hydrogen production test. The amount of H2 released was detected on a gas chromatograph with nitrogen as carrier gas every hour.
[0079] Comparative Example 3
[0080] The preparation of two-dimensional bimetallic porphyrin MOF (ZnTCuM) photocatalyst material, the specific steps are as follows:
[0081] (I) Preparation of two-dimensional bimetallic porphyrin MOF (ZnTCuM):
[0082] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, labeled as mixture 1. Subsequently, 100 mg (0.587 mmol) of CuCl2·2H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1. The reaction was monitored using UV-visible spectroscopy until the spectrum no longer changed. Then, 100 mg (0.336 mmol) of Zn(NO3)2·6H2O dissolved in 5 mL of ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried in a vacuum oven at 60 ° C overnight to obtain ZnTCuM.
[0083] (II) Photocatalytic hydrogen evolution experiment
[0084] At room temperature, 10 mg ZnTCuM was added to an aqueous solution containing 50 mL deionized water and 10 mL triethanolamine (sacrificial agent), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0085] Comparative Example 4
[0086] The preparation of the two-dimensional metalloporphyrin MOFs (ZnTZnMT) photocatalyst with a uniform TiO2 nanoparticle layer is mostly the same as that in Example 1, except that the addition of CuCl2·2H2O in step (1) of Example 1 is omitted. The specific steps are as follows:
[0087] (I) Preparation of two-dimensional metalloporphyrin MOF (ZnTZnM)
[0088] 40 mg (0.049 mmol) TCPP and 25 mg (0.205 mmol) benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL DMF and heated at 150 ° C, marked as mixture 1. Then, 100 mg (0.336 mmol) Zn (NO3) 2·6H2O dissolved in 5 mL ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and subsequently dried in a vacuum oven at 60 ° C overnight to obtain ZnTZnM.
[0089] (II) Preparation of two-dimensional metalloporphyrin MOFs (ZnTZnMT) with uniform TiO2 nanoparticle layer
[0090] 8 mg of ZnTZnM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 100 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The obtained solid was separated by centrifugation and washed with ethanol 3 times. The obtained solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and washed 3 times with anhydrous ethanol. The obtained solid was dried overnight in a vacuum oven at 60 ° C to obtain ZnTZnMT.
[0091] (III) Photocatalytic hydrogen evolution experiment
[0092] At room temperature, 10 mg ZnTZnMT was added to an aqueous solution containing 50 mL deionized water and 10 mL triethanolamine (TEOA, sacrificial agent), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp for photocatalytic hydrogen production test. The amount of H2 released was detected on a gas chromatograph with nitrogen as carrier gas every hour.
[0093] Comparative Example 5
[0094] A TiO2 nanoparticle and two-dimensional bimetallic porphyrin composite photocatalyst (ZnTCuM-TiO2), compared with Example 1, the main parts are the same, except that the TiO2 nanoparticles and the two-dimensional bimetallic porphyrin are directly mixed, and the specific steps are as follows:
[0095] (I) Preparation of ZnTCuM
[0096] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, labeled as mixture 1. Subsequently, 100 mg (0.587 mmol) of CuCl2·2H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1. The reaction was monitored using UV-visible spectroscopy until the spectrum no longer changed. Then, 100 mg (0.336 mmol) of Zn(NO3)2·6H2O dissolved in 5 mL of ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried in a vacuum oven at 60 ° C overnight to obtain ZnTCuM.
[0097] (II) Preparation of titanium oxide nanoparticles
[0098] 100 μL tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL ethanol, refluxed at 80 ° C for 1 hour (recorded as mixture B), centrifuged, and washed three times with ethanol. Subsequently, the obtained solid was added to a mixed solvent consisting of 8 mL H2O and 250 μL DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and a solvent thermal reaction was performed at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60 ° C vacuum oven to obtain TiO2 nanoparticles.
[0099] (III) Preparation of ZnTCuM-TiO2
[0100] 8mg ZnTCuM was dispersed in a 25ml round-bottom flask containing 8mL H2O and 4mL ethanol mixed solvent, ultrasonically treated for 30 minutes (recorded as mixture A), and the TiO2 nanoparticles prepared in step (ii) were added. The obtained solid was then dispersed in a mixed solvent consisting of 8mL H2O and 250μL DMF, and the mixed solution was poured into a 15mL stainless steel reactor with a polytetrafluoroethylene liner, and a solvent thermal reaction was carried out at 120°C for 12 hours. Finally, the product was collected by centrifugation at 7500rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60°C vacuum oven to obtain ZnTCuM-TiO2.
[0101] (III) Photocatalytic hydrogen evolution experiment
[0102] At room temperature, 10 mg of ZnTCuM-TiO2 was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0103] Comparative Example 6
[0104] A two-dimensional single metal porphyrin composite material photocatalyst (FeTMT) covered with an in-situ TiO2 nanoparticle layer, the preparation method of which comprises the following steps:
[0105] (I) Preparation of FeTM
[0106] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, which was marked as mixture 1. Subsequently, 100 mg (0.248 mmol) of Fe(NO3)3·9H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1 within 5 min. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried in a vacuum oven at 60 ° C overnight to obtain FeTM.
[0107] (II) Preparation of FeTMT
[0108] 8 mg of FeTM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 200 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The resulting solid was separated by centrifugation and washed with ethanol 3 times. The resulting solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60 ° C vacuum oven to obtain FeTMT.
[0109] (III) Photocatalytic hydrogen evolution experiment
[0110] At room temperature, 10 mg of FeTMT was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0111] Comparative Example 7
[0112] A two-dimensional single metal porphyrin composite photocatalyst (AlTMT) covered with an in-situ TiO2 nanoparticle layer, the preparation method of which comprises the following steps:
[0113] (I) Preparation of AlTM
[0114] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, which was marked as mixture 1. Subsequently, 100 mg (0.266 mmol) of Al (NO3) 3 · 9H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1 within 5 min. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried overnight in a vacuum oven at 60 ° C to obtain AlTM.
[0115] (II) Preparation of AlTMT
[0116] 8 mg of AlTM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 200 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The obtained solid was separated by centrifugation and washed with ethanol 3 times. The obtained solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60 ° C vacuum oven to obtain AlTMT.
[0117] (III) Photocatalytic hydrogen evolution experiment
[0118] At room temperature, 10 mg of AlTMT was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0119] Comparative Example 8
[0120] A two-dimensional bimetallic porphyrin composite photocatalyst (FeTCuMT) covered with an in-situ TiO2 nanoparticle layer is substantially the same as Example 2, except that in step (i), 100 mg (0.336 mmol) of Zn(NO3)2·6H2O is adjusted to 100 mg (0.248 mmol) of Fe(NO3)3·9H2O. The preparation method thereof comprises the following steps:
[0121] (I) Preparation of FeTCuM
[0122] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, labeled as mixture 1. Subsequently, 100 mg (0.587 mmol) of CuCl2·2H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1 over 5 min. The reaction was monitored using UV-visible spectroscopy until the spectrum no longer changed. Then, 100 mg (0.248 mmol) of Fe(NO3)3·9H2O dissolved in 5 mL of ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried in a vacuum oven at 60 ° C overnight to obtain FeTCuM.
[0123] (II) Preparation of FeTCuMT
[0124] 8 mg of FeTCuM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 200 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The obtained solid was separated by centrifugation and washed with ethanol 3 times. The obtained solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60 ° C vacuum oven to obtain FeTCuMT.
[0125] (III) Photocatalytic hydrogen evolution experiment
[0126] At room temperature, 10 mg of FeTCuMT was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0127] Comparative Example 9
[0128] A two-dimensional bimetallic porphyrin composite photocatalyst (AlTCuMT) covered with an in-situ TiO2 nanoparticle layer is substantially the same as Example 2, except that in step (i), 100 mg (0.336 mmol) of Zn(NO3)2·6H2O is adjusted to 100 mg (0.266 mmol) of Al(NO3)3·9H2O. The preparation method thereof comprises the following steps:
[0129] (I) Preparation of AlTCuM
[0130] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, which was labeled as mixture 1. Subsequently, 100 mg (0.587 mmol) of CuCl2·2H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1 over 5 min. The reaction was monitored using UV-visible spectroscopy until the spectrum no longer changed. Then, 100 mg (0.266 mmol) of Al(NO3)3·9H2O dissolved in 5 mL of ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried in a vacuum oven at 60 ° C overnight to obtain AlTCuM.
[0131] (II) Preparation of AlTCuMT
[0132] 8 mg of AlTCuM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 200 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The resulting solid was separated by centrifugation and washed with ethanol 3 times. The resulting solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60 ° C vacuum oven to obtain AlTCuMT.
[0133] (III) Photocatalytic hydrogen evolution experiment
[0134] At room temperature, 10 mg of AlTCuMT was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0135] Comparative Example 10
[0136] A two-dimensional bimetallic porphyrin composite photocatalyst (CoTCuMT) covered with an in-situ TiO2 nanoparticle layer is substantially the same as Example 2, except that 100 mg (0.336 mmol) of Zn(NO3)2·6H2O is adjusted to 100 mg (0.344 mmol) of Co(NO3)2·6H2O in step (i). The preparation method thereof comprises the following steps:
[0137] (I) Preparation of CoTCuM
[0138] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C, which was labeled as mixture 1. Subsequently, 100 mg (0.587 mmol) of CuCl2·2H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1 over 5 min. The reaction was monitored using UV-visible spectroscopy until the spectrum no longer changed. Then, 100 mg (0.344 mmol) of Co(NO3)2·6H2O dissolved in 5 mL of ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried in a vacuum oven at 60 ° C overnight to obtain CoTCuM.
[0139] (II) Preparation of CoTCuMT
[0140] 8 mg of CoTCuM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 200 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The resulting solid was separated by centrifugation and washed with ethanol 3 times. The resulting solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60 ° C vacuum oven to obtain CoTCuMT.
[0141] (III) Photocatalytic hydrogen evolution experiment
[0142] At room temperature, 10 mg of CoTCuMT was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0143] Comparative Example 11
[0144] A two-dimensional bimetallic porphyrin composite photocatalyst (CuTCuMT) covered with an in-situ TiO2 nanoparticle layer is substantially the same as Example 2, except that in step (i), 100 mg (0.336 mmol) of Zn(NO3)2·6H2O is adjusted to 100 mg (0.414 mmol) of Cu(NO3)2·3H2O. The preparation method thereof comprises the following steps:
[0145] (I) Preparation of CuTCuM
[0146] 40 mg (0.049 mmol) of TCPP and 25 mg (0.205 mmol) of benzoic acid were dissolved in a 250 ml three-necked flask containing 100 mL of DMF and heated at 150 ° C. This was labeled as mixture 1. Subsequently, 100 mg (0.587 mmol) of CuCl2·2H2O dissolved in 5 mL of ethanol was added dropwise to mixture 1 over 5 min. The reaction was monitored using UV-visible spectroscopy until the spectrum no longer changed. Then, 100 mg (0.414 mmol) of Cu(NO3)2·3H2O dissolved in 5 mL of ethanol was added dropwise over 5 minutes. The resulting mixture was refluxed at 150 ° C until the spectrum remained unchanged. The resulting solid was then washed three times with ethanol and then dried overnight in a vacuum oven at 60 ° C to obtain CuTCuM.
[0147] (II) Preparation of CuTCuMT
[0148] 8 mg of CuTCuM was dispersed in a 25 ml round-bottom flask containing 8 mL of H2O and 4 mL of ethanol mixed solvent and ultrasonically treated for 30 minutes (recorded as mixture A). In addition, 200 μL of tetrabutyl titanate was dispersed in a 50 ml round-bottom flask containing 20 mL of ethanol and refluxed at 80 ° C for 1 hour (recorded as mixture B). Subsequently, mixture B was gradually added to mixture A and refluxed at 80 ° C for 4 hours. The resulting solid was separated by centrifugation and washed with ethanol 3 times. The resulting solid was then dispersed in a mixed solvent consisting of 8 mL of H2O and 250 μL of DMF, and the mixed solution was poured into a 15 mL stainless steel reactor with a polytetrafluoroethylene liner, and the solvent thermal reaction was carried out at 120 ° C for 12 hours. Finally, the product was collected by centrifugation at 7500 rpm and then washed 3 times with anhydrous ethanol. The obtained solid was then dried overnight in a 60 ° C vacuum oven to obtain CuTCuMT.
[0149] (III) Photocatalytic hydrogen evolution experiment
[0150] At room temperature, 10 mg of CuTCuMT was added to an aqueous solution containing 50 mL of deionized water and 10 mL of triethanolamine (sacrificial agent, TEOA), ultrasonicated for 10 minutes, and then poured into a 250 mL quartz reactor, and the reactor was bubbled with N2 for 10 minutes to remove O2. After that, the sample was stored under a 300 W Xe lamp (the spectral range of the lamp was 340 nm-780 nm) for photocatalytic hydrogen production testing. The amount of H2 released was detected on a gas chromatograph with nitrogen as the carrier gas every hour.
[0151] The photocatalysts prepared in Example 1 and Comparative Example 3 were characterized and tested. Figure 1 The nitrogen adsorption-desorption isotherms (BET) of ZnTCuM and ZnTCuMT. ZnTCuM shows a type I isotherm. The unclosed desorption curve in ZnTCuM may be due to the adsorption of the solvent (DMF) on the Zn-oxo clusters, resulting in strong N2 adsorption. ZnTCuMT shows a type IV isotherm under high pressure, with an obvious H3-type hysteresis loop, indicating the presence of a wedge-shaped mesoporous structure in the nanocomposite. The specific surface areas of ZnTCuM and ZnTCuMT were determined by the BET method. The results showed that the specific surface area of ZnTCuM was 311.69 m 2 / g, while the specific surface area of ZnTCuMT is reduced to 174.53m 2 / g, which is lower than that of the 2D metalloporphyrin MOFs (ZnTZnM) without TiO2 NPs layer, which may be due to the TiO2 NPs layer introduced onto ZnTCuM.
[0152] like Figure 2 The photocatalysts prepared in Example 1 and Comparative Examples 1-4 show the hydrogen evolution kinetic curves in 50 mL TEOA aqueous solution (50 mL deionized water and 10 mL TEOA). It can be clearly seen that the ZnTCuMT photocatalyst of Example 1 has the best hydrogen evolution effect. After 6 hours of illumination, pure TiO2, separate ZnTZnM and ZnTCuM produce 1.33 mmol g -1 H2, ZnTZnMT produced 2.93 mmol g -1 H2, under the same conditions, the two-dimensional metalloporphyrin MOFs (ZnTCuMT) with a uniform TiO2 nanoparticle layer on the surface can precipitate 18.55 mmol g -1 The hydrogen production was 13.9 times that of Examples 1-3 and 6.3 times that of Example 4, indicating that the uniform growth of a TiO2 NPs layer on the surface of two-dimensional metalloporphyrin MOFs (ZnTCuMT) can significantly improve the photocatalytic activity of MOFs.
[0153] like Figure 3The hydrogen evolution kinetic curves of ZnTCuMT, FeTCuMT, AlTCuMT, CoTCuMT, and CuTCuMT photocatalysts prepared in Example 2 and Comparative Examples 8 to 11 in 50 mL of deionized water and 10 mL of TEOA are shown in Figure 2. 2+ As a metal linking site, the obtained ZnTCuMT has higher photocatalytic activity than FeTCuMT, AlTCuMT, CoTCuMT, and CuTCuMT. The change in activity is mainly due to the different coordination between the metal ions as linkers and carboxyl groups in porphyrin and the charge separation. 2+ In porphyrin, it usually forms a stable coordination bond with the nitrogen atom of porphyrin with strong coordination, which can better promote electron transfer, enhance the electron separation efficiency, and reduce the recombination rate during the photocatalytic process, thereby improving the efficiency of the photocatalytic reaction. 2+ It has a lower electronegativity, which means it can more easily accept electrons, thereby enhancing the separation and conduction of photogenerated carriers and reducing the recombination of electrons. 2+ Ions have relatively ideal electronegativity and delocalization characteristics, which can effectively promote the transfer of electrons and reduce the recombination of electrons and holes. They also have high efficiency in capturing and migrating photogenerated electrons, and therefore exhibit superior activity in photocatalytic reactions.
[0154] Fe 3+ As a strong oxidant, the structure formed by coordination in porphyrin is relatively stable, but Fe 3+ The high charge and strong coordination strength of Fe may limit the rapid transfer of electrons, resulting in a higher carrier recombination rate during the photocatalytic process and reducing the photocatalytic activity. 3+ The oxidizing property of Zn is strong, but it does not necessarily promote the migration of electrons effectively, which may lead to a lower catalytic efficiency than Zn 2+ .Al 3+ Usually as a center with strong Lewis acidity, coordination with porphyrin may lead to high structural rigidity, limiting the rapid migration and separation of photogenerated carriers. 3+ The high charge of Fe and Al leads to a strong interaction with the ligand, which also affects the efficiency of electron transfer. Fe and Al, two metal ions, have a strong charge density, but their electronegativity is high, which may lead to a more serious recombination of electrons and holes, thus affecting the efficiency of photocatalysis.
[0155] Co 2+ The coordination effect in porphyrin is strong, but due to its lower electronegativity and weaker oxidizing property, it may not be as 2+ It does not effectively promote the transfer of electrons, resulting in a catalytic efficiency that is not as good as that of Zn 2+ ,Co 2+The low electronegativity and oxidizing property of the photocatalyst result in a slow electron transfer rate, which in turn limits the rate of the photocatalytic reaction.
[0156] Cu 2+ ions have strong oxidizing properties and can promote electron transfer after coordination with porphyrin. 2+ It is susceptible to self-reduction in the photocatalytic reaction, resulting in fluctuations in its catalytic performance. 2+ In comparison, Cu 2+ The electron transfer efficiency of Zn 2+ Stable because it is more prone to electron recombination. Cu 2+ Although it can promote electron transfer, it is easy to undergo self-reduction reaction, which may lead to recombination of carriers and thus affect the catalytic efficiency. 2+ In comparison, Cu 2+ The electron transfer efficiency of Zn is low. 2+ The electronic structure of Zn enables it to effectively participate in the electron transfer in the photocatalytic reaction and does not easily undergo self-reduction reaction. 2+ It can also effectively interact with the electron cloud in porphyrin through its lower electronegativity, thereby improving the catalytic activity. 3+ 、Co 2+ 、Al 3+ , Cu 2+ The electronic structure of Cu ions causes them to attract electrons too strongly during photocatalysis (leading to electron recombination) or to be unstable under certain conditions (e.g. 2+ These factors make their photocatalytic activity relatively low.
[0157] In general, Zn 2+ Due to its excellent electron transfer ability, stable coordination and low recombination rate, ZnTCuMT exhibits the best photocatalytic activity among the five photocatalytic materials. 3+ 、Co 2+ 、Al 3+ and Cu 2+ However, their photocatalytic activity is inferior to that of ZnTCuMT due to lower electron transfer efficiency or more serious electron recombination, indicating that there is a stronger synergistic effect between the Zn linker and the copper metalloporphyrin ligand in MOF, resulting in the best hydrogen production rate.
[0158] Figure 4 The hydrogen evolution kinetic curves of FeTMT and FeTCuMT photocatalysts in 50 mL of deionized water and 10 mL of TEOA. Figure 5The hydrogen evolution kinetic curves of AlTMT and AlTCuMT photocatalysts in 50 mL deionized water and 10 mL TEOA. 3+ or Fe 3+ As a connector, the assembled porphyrin MOFs (AlTM and FeTM) were also coated on the TiO2 NPs layer, named AlTMT and FeTMT, respectively. Their photocatalytic activities were lower than those of AlTCuMT and FeTCuMT with TCPP (Cu) as ligand. The activity of AlTCuMT was 9.29 times higher than that of AlTMT-200, and the activity of FeTCuMT was 1.27 times higher than that of FeTMT-200. These results indicate that the Cu at the center of the TCPP macrocyclic ring 2+ It can serve as an additional active site for photocatalytic hydrogen production to further increase the hydrogen production rate.
[0159] like Figure 6 Comparison of hydrogen evolution rates of TiO2, ZnTCuM, ZnTCuMT, and ZnTCuM-TiO2 photocatalysts in 50 mL TEOA aqueous solution. The hydrogen evolution rate of pure TiO2 is 174.1 μmol g -1 h -1 The hydrogen evolution rate of ZnTCuM is 290.2 μmol g -1 h -1 The hydrogen evolution rate of ZnTCuM-TiO2 is 1462.9 μmol g -1 h -1 , while the photocatalytic hydrogen evolution rate of ZnTCuMT was 3035.5 μmol g -1 h -1, 10.5 times higher than ZnTCuM, 17.4 times higher than pure TiO2, and 2.1 times higher than ZnTCuM-TiO2. This may be due to the fact that electrons can be transferred both to the aggregated TiO2 NPs and between the TiO2 NPs layers. This also indicates that in the constructed target material, the TiO2 NPs layer on the surface of ZnTCuM can serve as a hydrogen evolution active site and a protective layer. Moreover, due to the effective separation and migration of electron-hole pairs, the photocatalytic hydrogen production activity of the target nanocomposite is significantly improved and the performance is stable, providing a new approach for constructing highly efficient and stable organic-inorganic nanocomposite photocatalytic materials. In the two-dimensional bimetallic porphyrin composite covered with an in-situ TiO2 nanoparticle layer, the active TiO2 NPs layer grows in-situ on the two-dimensional bimetallic porphyrin MOFs, effectively protecting the two-dimensional bimetallic porphyrin MOFs from corrosion, improving its photocatalytic stability and charge separation. At the same time, the two-dimensional bimetallic porphyrin MOFs increase the visible light absorption, and the multi-metal centers provide more active sites. Moreover, the moderately TiO2 NPs layer tightly bound to the two-dimensional bimetallic porphyrin MOFs sheets can improve the electron transfer of the composite photocatalyst. Compared with similar photocatalytic materials, its photocatalytic hydrogen evolution activity and stability are significantly improved.
[0160] To gain an in-depth understanding of the photocatalytic hydrogen evolution of ZnTCuMT, the separation and transfer of interfacial charges were investigated. As Figure 7 are the fluorescence spectra of TiO2, ZnTCuM, ZnTCuMT, and ZnTCuM-TiO2 photocatalysts. TiO2 exhibits strong fluorescence due to its high surface states, and its fluorescence intensity is much higher than that of ZnTCuMT, ZnTCuM, and ZnTCuM-TiO2. Under the same conditions, the fluorescence of the samples shows ZnTCuMT < ZnTCuM < ZnTCuM-TiO2 < TiO2, indicating that coating the TiO2 NPs layer on ZnTCuM can effectively improve the charge separation in the ZnTCuMT nanocomposite.
[0161] As Figure 8Shown is a comparison of the photocurrent spectra of TiO2, ZnTCuM, ZnTCuMT, and ZnTCuM-TiO2 photocatalysts. The transient photocurrent spectra show that pure ZnTCuM and TiO2 exhibit lower photocurrent responses due to higher charge recombination or narrow photoresponse. Importantly, ZnTCuMT shows an enhanced transient photocurrent density. In addition, the transient photocurrent density of ZnTCuMT is also higher than that of ZnTCuM-TiO2, indicating that the coupling of ZnTCuM with the TiO2NPs layer can effectively promote the separation and transfer of carriers. The different trends of ZnTCuMT from ZnTCuM and TiO2 may be due to the gradual generation (gradual enhancement of photocurrent in ZnTCuMT) or recombination (gradual weakening of photocurrent in ZnTCuM) of some photoinduced electrons and holes during irradiation.
[0162] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer, characterized in that: Tetrabutyl titanate is mixed with two-dimensional bimetallic porphyrin MOFs in a first solvent system and heated to reflux, and the obtained solid product is subjected to solvothermal reaction in a second solvent system to obtain a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer, and the reaction is completed.
2. The method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer according to claim 1, characterized in that: The mass volume ratio of the two-dimensional bimetallic porphyrin MOFs to tetrabutyl titanate is 2:25-100 mg / μL.
3. The method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer according to claim 1, characterized in that: The mixture is heated under reflux at a temperature of 60 to 120°C; The first organic solvent used in the first solvent system includes a mixture of water and ethanol; The second organic solvent used in the second solvent system includes a mixture of water and N,N-dimethylformamide; In the solvothermal reaction, the temperature is 100-150°C.
4. The method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer according to claim 1, characterized in that: The preparation process of the two-dimensional bimetallic porphyrin MOFs is as follows: TCPP, benzoic acid, copper salt and zinc salt are mixed in a third organic solvent, and heated under reflux reaction to obtain the two-dimensional bimetallic porphyrin MOFs.
5. The method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer according to claim 4, characterized in that: The copper salts include copper chloride and copper nitrate; The zinc salts include zinc nitrate and zinc chloride; The third organic solvent includes N,N-dimethylformamide, ethanol or a mixture thereof; The molar ratio of TCPP, benzoic acid, copper salt and zinc salt is 1:(2-6):(7-14):(4-10); The molar volume ratio of TCPP to the third organic solvent is 1:2-3 mmol / L; During the heating reflux reaction, the reaction temperature is 120-180°C.
6. The method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer according to claim 1, characterized in that: Tetrabutyl titanate is dispersed in a fourth organic solvent and preheated, wherein the fourth organic solvent comprises ethanol.
7. The method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer according to claim 1, characterized in that: The preheating temperature of the tetrabutyl titanate is 50-100°C.
8. The method for preparing a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer according to claim 1, characterized in that: Tetrabutyl titanate is preheated, mixed with two-dimensional bimetallic porphyrin MOFs in a first solvent system, heated to reflux, and centrifuged to obtain a solid product, which is washed. The washed solid product is subjected to a solvothermal reaction in a second solvent system, and the product is collected by centrifugation, washed, and dried to obtain a two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer, and the reaction is completed.
9. A two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer, prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the two-dimensional bimetallic porphyrin composite material covered with an in-situ TiO2 nanoparticle layer as claimed in claim 9 in the field of photocatalytic hydrolysis to produce hydrogen.
Citation Information
Patent Citations
Preparation method and applications of functional coordination polymer
CN104324760A
Ruthenium-doped ultrathin TiO2 nanosheet photocatalyst and application thereof in photocatalytic water decomposition hydrogen production
CN112473638A
Platinum-doped ultrathin Zr-MOFs nanometer thin-layer composite photocatalyst as well as preparation method and application thereof
CN113398997A